Severe traumatic brain injury is associated with a unique coagulopathy phenotype. Issue 4 (April 2019) - Samuels, Jason M.; Moore, Ernest E.; Silliman, Christopher C.; Banerjee, Anirban; Cohen, Mitchell J.; Ghasabyan, Arsen; Chandler, James; Coleman, Julia R.; Sauaia, Angela
Abstract : BACKGROUND: Traumatic brain injury (TBI) patients present on a spectrum from hypocoagulability to hypercoagulability, depending on the injury complexity, severity, and time since injury. Prior studies have found a unique coagulopathy associated with TBI using conventional coagulation assays such as INR; however, few studies have assessed the association of TBI and coagulopathy using viscoelastic assays that comprehensively evaluate the coagulation in whole blood. This study aims to reevaluate the TBI-specific trauma-induced coagulopathy using arrival thrombelastography. Because brain tissue is high in key procoagulant molecules, we hypothesize that isolated TBI is associated with procoagulant and hypofibrinolytic profiles compared with injuries of the torso, extremities, and polytrauma, including TBI. METHODS: Data are from the prospective Trauma Activation Protocol study. Activated clotting time (ACT), angle, maximum amplitude (MA), 30-minute percent lysis after MA (LY30), and functional fibrinogen levels (FFLEV) were recorded. Patients were categorized into isolated severe TBI (I-TBI), severe TBI with torso and extremity injuries (TBI + TORSO/EXTREMITIES), and isolated torso and extremity injuries (I-TORSO/EXTREMITIES). Poisson regression was used to adjust for multiple confounders. RESULTS: Overall, 572 patients (48 I-TBI, 45 TBI + TORSO/EXTREMITIES, 479 I-TORSO/EXTREMITIES) were included in this analysis. The groups differed in INR, ACT, angle, MA, and FFLEV but not in 30-minute percent lysis. When compared with I-Torso/Extremities, after adjustment for confounders, severe I-TBI was independently associated with ACT less than 128 seconds (relative risk [RR], 1.5; 95% confidence interval [CI], 1.1–2.2), angle less than 65 degrees (RR, 2.2; 95% CI, 1.4–3.6), FFLEV less than 356 (RR, 1.7; 95% CI, 1.2–2.4) but not MA less than 55 mm, hyperfibrinolysis, fibrinolysis shutdown, or partial thromboplastin time (PTT) greater than 30. CONCLUSION: Severe I-TBI was independently associated with a distinct coagulopathy with delayed clot formation but did not appear to be associated with fibrinolysis abnormalities. Low fibrinogen and longer ACT values associated with I-TBI suggest that early coagulation factor replacement may be indicated in I-TBI patients over empiric antifibrinolytic therapy. Mechanisms triggering coagulopathy in TBI are unique and warrant further investigation. LEVEL OF EVIDENCE: Retrospective cohort study, prognostic, level III.